Profile of Ophthalmological Diseases in Out-Patients of Shree Birendra Hospital - Bist, Ramesh Raj; Rajkarnikar, Sagar; Gurung, Anu; Chetry, Pratik (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: The causes of blindness and the pattern of eye diseases differ in developing and developedcountries and often in communities. A study of the pattern of ocular diseases is very important because whilesome eye conditions are just causes of ocular morbidity others invariably lead to blindness. Methods: This was a retrospective study including all the cases which attended the department of Ophthalmologyof Shree Birendra Hospital in April 2010 to April 2011. Results: A total of 17988 patients were seen during the study period with mean age 39.95 ± 18.94 years, maleto female ratio of 51.02: 48.92% in the department of Ophthalmology. Among them 4779 were regular servingarmy personnel and 13209 were ex-army and army families. The largest number of cases were seen in lensrelated disease (25.19%), followed by conjunctival and scleral disease (24.29%). Conclusions: The pattern of eye disease varies in different age groups. In younger age group conjunctival,scleral disease and refractive error were commonly seen whereas in elder age group lens disorder was frequentlyseen. The number of blind patients was more in females than in male patients. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12917